Using MATLAB to Optimize UWEC Class Schedule Building - Brake, Danielle; Brisbin, Abra; Walgurski, Nathan; Pinter, Nathan; Mallmann, Eric; Kemp, John; Arneson, Claire (My University, 2018)
As courses fill up during student registration, the College of Arts and Sciences needs to open new sections. MATLAB, a programming language that implements the use of mathematical functions, was used to create a model to help the College of Arts and Sciences find the optimal time to open a new course section. This model finds the optimal time by comparing the estimated number of available students at each proposed time slot.
Color poster with text and charts.
Keywords: Posters; MATLAB; Class schedules; Mathematics; University classes